Karimov, Ayyub - (:unkn) unknown (My University, 2026)
Karimov Ayyub was born on April 26, 1958, in Birinci Şahsevən village, Beylagan District, Azerbaijan Republic. In 1979, he enrolled in the Faculty of History at Baku State University, He graduated from that faculty with honors in 1984. Since 1990, he has worked at the Azerbaijan Technical University's Department of Philosophy and Political Science as a senior laboratory assistant, office manager, instructor, senior instructor, associate professor, and from 2011 to 2015 years, he served as head of the department. In 2014, he defended his doctoral dissertation at the Dissertation Council of the Institute of Philosophy, Sociology, and Law of the National Academy of Sciences of Azerbaijan, In 2017, he was awarded the Doctor of Philosophy degree. He is currently a professor at the Department of Humanities at AzTU. He is the author of 143 scientific articles, teaching materials, 2 textbooks, and 3 monographs. In addition, he is the author of “Sociology of Social Institutions” (textbook, Baku, 1994); “Political Science in Schemes and Tables” (co-authored with I. Abdullayev), textbook, Baku, 2000; the textbook “National and International Environmental Protection Policy” for the European Union's TEMPUS project, Baku, 2007, and “Democracy: The Present and Future of Humanity, a Social-Philosophical Approach,” Baku, Elm Publishing House, 2009. The 388-page monograph has been published. The textbooks “Modern Philosophical Currents: A Social-Philosophical Analysis,” “The Social-Philosophical Aspects of Human-Nature Relations,” and “Philosophy” have been recommended for publication. I took first place in the “Philosophical Discourse” competition of the “Association of Philosophy and Social-Political Sciences of Azerbaijan” and was awarded a first-degree diploma by the association on January 22, 2011. I have successfully completed a course at the Sorbonne University of France, organized by our Ministry of Education, and was awarded a certificate by the French Ambassador. By order K-1375 of the Ministry of Education of the Republic of Azerbaijan dated December 30, 2020, I was awarded the “ADVANCED EDUCATION WORKER OF THE REPUBLIC OF AZERBAIJAN” BADGE.
Keywords: Philosophy